PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CASE METHOD MENGGUNAKAN GOOGLE SLIDE PADA PEMBELAJARAN IPAS KELAS IV SD - Nasution, Nurul Hasanah; Rozi, Fahrur; Nurmayani, Nurmayani; Gandamana, Apiek; Prawijaya, Septian (Universitas Negeri Medan, 2024)
This research was conducted based on problems, namely, teachers do not use learning media during learning activities, teachers lack understanding and skill in developing technology-based learning media, teachers do not understand how to make learning media appropriate to learning, teachers do not use various learning models in the learning process. , students become passive because learning activities still focus on the teacher's explanation. The aim of this research is to determine the validity of the appropriateness of the material, the appropriateness of the media, to determine the practicality of the media, to determine the effectiveness of Case Method-based learning media using Google Slides which was developed for elementary school students in class IV SDN 158490 Aek Tolang 2 T.P 2023/2024. The research method used is the 4D development model, which consists of Define, Design, Development and Dissemination. The results of the validation research for material experts, media experts and practicality experts were 81%, 87%, 86% with qualifications that were very feasible and practical to use without revision. The results of the pre-test and post-test carried out in class IV showed that the results of the 16 students who took the pre-test were 11 students who had not completed it and 4 students who had completed it with a percentage of 57.8%, while the results of the post-test were 16 students. which is 89% complete. Based on class completeness calculations, the media effectiveness presentation was 87.5% with completeness criteria of 81%-100% categorized as very effective.